Effect of carbon nanotubes on the strength of adhesive lap joints of C/C and C/CSiC ceramic fibre composites - Srivastava V.K. (My University, 2025)
Similar substrates of carbon/carbon (C/C) and carbon/carbonsilicon carbide (C/CSiC) composites were bonded with pure epoxy resin and the one containing 3% multiwall carbon nanotubes (MWCNTs). The results show that MWCNT/filled epoxy resin bonded C/CC/C and C/CSiCC/CSiC substrates have a higher adhesive joint strength than those bonded with epoxy resin alone. MWCNTs increase the toughness and strength of the epoxy resin, which increases the interface bond strength between two similar matching surfaces. © 2011 Elsevier Ltd. All rights reserved.